Pengaruh Ukuran Dan Jumlah Elemen Singular Terhadap Harga Faktor Intensitas Tegangan Untuk Kasus Retak Pojok Eliptik Dengan Metode Elemen Hingga - Wajan Berata; Nurul Muhayat (Institute of Research and Community Outreach, Petra Christian University, 2004)
Stress intensity factor evaluation is needed to evaluate residual strength and crack growth. It developes some methods to evaluate stress intensity factor. In this research, the stress intensity factor is evaluated on the case of part through crack in finite solid with configuration of quarter elliptic corner crack. It is done by ANSYS software which based on finite element method. Crack tip element model is chosen a quarter point isoparametric 20 node three dimension. The result of ANSYS analysis gives the geometry factor (â) close enough to geometry factor (â) of BEASY software result, with maximum error of 7.99% for the 90o - angle. On the other side, comparation of the ANSYS result with the result of Newmann-Raju equation, the error maximum is 3.89% for the 0o -angle. From statistical test is known that the selection of singular element size and number, disposed doesn't seem to influence the result of stress intensity factor calculation.